Potential of Nahar (Mesua ferrea) seed oil for industrial applications - Adewale, Ahmed Idris; Mirghani, Mohamed Elwathig Saeed; Muyibi, Suleyman Aremu; Daoud, Jamal Ibrahim; Abimbola, Mikail Maryam (2010)
The increasing demand for oils both for human consumption and for industrial applications has culminated into an increasing need to search for oils from non-conventional sources to augment the available ones and also to meet specific applications. Mesua ferrea L. (Guttiferae), penaga lilin (Malay) is a moderate sized tree of tropical Asia. The dehulling of nahar seed showed that the hull: kernel is 30:70, the proximate analysis of the seed kernel revealed that the seed kernel contained 3.55±0.50% moisture content, 76±2 % crude oil, 1.50±0.20% crude protein, 1.25±0.20% ash content and 17.70 ±0.73% carbohydrate, while the hulls, contained 13.50±0.50% moisture content, 1.30±0.20% crude oil, 3.40 ±0.20% crude protein, 0.65±0.05% ash content and 81.15 ±0.24% carbohydrate. The antimicrobial assay of the oils obtained from the kernel (using soxhlet and mechanical extraction techniques) and the oil obtained from the hull using soxhlet extraction showed a remarkable inhibition zone against all the tested bacteria (Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus).